2018
DOI: 10.1007/s00253-018-9190-3
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing catalytic stability and cadaverine tolerance by whole-cell immobilization and the addition of cell protectant during cadaverine production

Abstract: A whole-cell (cadaverine-producing strain, Escherichia coli AST3) immobilization method was developed for improving catalytic activity and cadaverine tolerance during cadaverine production. Cell-immobilized beads were prepared by polyvinyl alcohol (PVA) and sodium alginate (SA) based on their advantages in biocatalyst activity recovery and mechanical strength. The following optimal immobilization conditions were established using response surface methodology: 3.62% SA, 4.71% PVA, 4.21% CaCl, calcification, 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Therefore, the site-specific mutagenesis of butanol dehydrogenase ( butA ) gene might be further improved the AC and 2,3-BD yield and selectivity in C. creantum . In addition, although the repeated batch biocatalysis showed a high average productivity for AC and 2,3-BD production, the catalytic efficiency significantly deceased after only two batches, which can be further improved by cell immobilization to increase the cell viability and stability [44, 45]. On the other hand, process engineering, including buffer optimization, substrate concentration optimization, multiple biocatalysis strategies, and high cell density et al, can further improve AC and 2,3-BD production for commercial development.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the site-specific mutagenesis of butanol dehydrogenase ( butA ) gene might be further improved the AC and 2,3-BD yield and selectivity in C. creantum . In addition, although the repeated batch biocatalysis showed a high average productivity for AC and 2,3-BD production, the catalytic efficiency significantly deceased after only two batches, which can be further improved by cell immobilization to increase the cell viability and stability [44, 45]. On the other hand, process engineering, including buffer optimization, substrate concentration optimization, multiple biocatalysis strategies, and high cell density et al, can further improve AC and 2,3-BD production for commercial development.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that E. coli AST3 can be entrapped and immobilized successfully in a mixture of 3.62% sodium alginate and 4.71% polyvinyl alcohol by dripping into 4.21% CaCl 2 . 99 The results showed that the activity of the cells was reduced by the high concentration of cadaverine. Then the cell protectant polyvinylpyrrolidone (PVP) was found to improve the stability of the immobilized cells in 2 h (1.8-fold higher than the free cells).…”
Section: Process Intensification For Cadaverine Productionmentioning
confidence: 97%
“…In the reactor, the PVA-SA-PVP-immobilized E. coli AST3 could produce 146 g L −1 cadaverine with an over 98% molar conversion yield of l -lysine. 99 The immobilization of free lysine decarboxylase could be another strategy to improve the catalytic efficiency. It is interesting to see that the CadA can be in situ immobilized by the molecular biology technology.…”
Section: Process Intensification For Cadaverine Productionmentioning
confidence: 99%
“…Recently, some researchers reported that the inhibitory effect of cadaverine significantly limits cadaverine production [ 16 ]. In E. coli , a high level of intracellular cadaverine was confirmed to induce closing of porins, causing inadequate cell absorption of nutrients, and reducing cell growth and metabolism [ 17 ].…”
Section: Introductionmentioning
confidence: 99%